Collaborative Multi-racial Post-election Survey (CMPS), 2008 - Barreto, Matt A. ([Verlag nicht ermittelbar], 2014)
The 2008 Collaborative Multi-racial Post-election Survey (CMPS) is a national telephone survey of registered voters, with comparably large samples of African Americans, Asian Americans, Latinos, and Whites. The telephone survey, conducted between November 9, 2008 and January 5, 2009, is the first multiracial and multilingual survey of registered voters across multiple states and regions in a presidential election. In contrast to the 2008 American National Election Study (ANES) which oversampled Black and Latino voters, and was available in Spanish, the CMPS was available in six languages and contains robust samples of the four largest racial/ethnic groups: Whites, Latinos, Blacks, Asians. The CMPS contains 4,563 respondents who registered to vote in the November 2008 election and who self-identified as Asian, Black, Latino, and White. The survey was available in English, Spanish, Mandarin, Cantonese, Korean, Vietnamese and respondents were offered the opportunity to interview in their language of choice. The six states that were sampled to produced robust samples of all four major racial groups include California, Texas, New York, Florida, Illinois, and New Jersey, and the statewide samples range from 243 to 669 cases. In order to arrive at more nationally representative samples of each minority group, the study added two supplemental states per racial group, including Arizona and New Mexico (Latinos), North Carolina and Georgia (Blacks), Hawaii and Washington (Asians). Of these 12 states, 3 were considered political battlegrounds in the 2008 Presidential electorate -- New Mexico, Florida, and North Carolina. In order to examine multi-racial politics in competitive and non-competitive environments, the study supplemented the sample with six additional diverse battleground states: Colorado, Michigan, Nevada, Ohio, Pennsylvania, and Virginia. As of the 2008 election, two-thirds of the national electorate was concentrated in these 18 states. For Latinos, 92 percent of all registered voters reside in these states; 87 percent of Asian Americans; and 66 percent of Blacks, and 61 percent of Whites. The November 2008 CMPS provides estimates of the registered voter population by race, age, gender, and education level which was applied to the sample, by racial group, so that the distributions match those of the Census on these important demographic categories. In the study, there are 51 items dealing with sociopolitical attitudes, mobilization and political activity. Additionally, there are 21 items that capture demographic information, including: age, ancestry, birthplace, education, ethnicity, marital status, number in the household, religiosity, gender, media usage and residential context.